2017
DOI: 10.1210/jc.2017-01039
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Circulating RET M918T Mutated Tumor DNA in Patients With Advanced Medullary Thyroid Carcinoma

Abstract: Liquid biopsy is able to detect RET M918T mutations in patient plasma with high specificity but low sensitivity. In patients with established somatic RET M918T mutations, the allelic fraction of circulating tumor DNA is prognostic for overall survival and may play a role in monitoring response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 37 publications
3
49
0
5
Order By: Relevance
“…So far, only a few studies investigated the role of ctDNA in thyroid cancer. Cote et al 59 measured the ctDNA for RET M918T mutation in patients with medullary thyroid carcinoma (MTC) through droplet digital PCR and found the detection of RET M918T ctDNA strongly correlated with worse overall survival and more accurately predicted a worse outcome than calcitonin doubling time. Sandulache et al 60 tested anaplastic thyroid carcinoma (ATC) and found that the concordance between the tumor and cfDNA was high for BRAF , PIK3CA , NRAS and PTEN , and moderate for TP53 .…”
Section: Discussionmentioning
confidence: 99%
“…So far, only a few studies investigated the role of ctDNA in thyroid cancer. Cote et al 59 measured the ctDNA for RET M918T mutation in patients with medullary thyroid carcinoma (MTC) through droplet digital PCR and found the detection of RET M918T ctDNA strongly correlated with worse overall survival and more accurately predicted a worse outcome than calcitonin doubling time. Sandulache et al 60 tested anaplastic thyroid carcinoma (ATC) and found that the concordance between the tumor and cfDNA was high for BRAF , PIK3CA , NRAS and PTEN , and moderate for TP53 .…”
Section: Discussionmentioning
confidence: 99%
“…10 Given Furthermore, its use in a patient with advanced sMTC with a confirmed somatic RET M918T mutation resulted in tumour regression, a drop in serum calcitonin and symptom improvement. 10 Given Furthermore, its use in a patient with advanced sMTC with a confirmed somatic RET M918T mutation resulted in tumour regression, a drop in serum calcitonin and symptom improvement.…”
Section: Somatic Ret Mutationsmentioning
confidence: 95%
“…32 The M918T-mutated tumour DNA can also be identified in peripheral blood, and there is some evidence that circulating M918T-mutated DNA portends a worse overall survival and more accurately predicts outcome than calcitonin doubling time. 10 Given the established role of RET in hMTC and that almost half of sMTCs harbour somatic RET mutations, most efforts at novel drug development have focussed on inhibiting RET and RET-related pathways ( Figure 2). This has resulted in the licensing of tyrosine kinase inhibitors (TKI) with specificity for RET, vandetanib and cabozantinib.…”
Section: Somatic Ret Mutationsmentioning
confidence: 99%
“…A rapid method for DNA extraction from FNB for RET mutation analysis by PCR with the intention of targeted therapy was developed in 1998 (291). Furthermore, in the recent study by Cote et al (292) the presence of somatic RET mutation in plasma was evaluated in 50 patients with RET p.M918T mutations detected in tumor tissue. In 16 of these patients the somatic RET mutation was detected in circulating cell-free DNA in plasma and by a blood test.…”
Section: Molecular Biology In Mtcmentioning
confidence: 99%